Effects of feeding transgenic corn with mCry1Ac or maroACC gene to laying hens for 12 weeks on growth, egg quality and organ health. (26th February 2016) - Zhong, R. Q.; Chen, L.; Gao, L. X.; Zhang, L. L.; Yao, B.; Yang, X. G.; Zhang, H. F.
Abstract : The objective of the present study was to investigate the effect of feeding two transgenic corn lines containing the mCry1Ac gene from Bacillus thuringiensis strain (BT-799) and the maroACC gene from Agrobacterium tumefaciens strain (CC-2), respectively, on growth, egg quality and organ health indicators. Expression of the mCry1Ac gene confers resistance to Pyrausta nubilalis and the maroACC gene confers tolerance to herbicides. Healthy hens ( n =96 placed in cages; 3 hens/cage) were randomly assigned to one of four corn–soybean meal dietary treatments (8 cages/treatment) formulated with the following corn: non-transgenic near-isoline control corn (control), BT-799 corn, CC-2 corn and commercially available non-transgenic reference corn (reference). The experiment was divided into three 4-week phases (week 1 to 4, week 5 to 8 and week 9 to 12), during which hens were fed mash diets. Performance (BW, feed intake and egg production) and egg quality were determined. Following slaughter at the end of 12 weeks of feeding ( n =8/treatment), carcass yield and organ weights (heart, liver, spleen, lung, kidneys, stomach and ovary) were recorded; organs and intestines were sampled for histological analysis. Analysis of serum biochemistry parameters to assess the liver and kidney function were performed. No differences in BW, egg production and production efficiency were observed between hens consuming the control diet and hens consuming the BT-799 or CC-2 diet. Haugh unit measures and egg component weights were similar between the control and test groups. Carcass yield was not affected by the diet treatment. Similar organosomatic indices and serum parameters did not indicate the characteristics of organ dysfunction. All observed values of the BT-799 and CC-2 groups were within the calculated tolerance intervals. This research indicates that the performance, egg quality, organ health and carcass yield of laying hens fed diets containing the BT-799 or CC-2 corn line were similar to that of laying hens fed diets formulated with the non-transgenic near-isoline corn with comparable genetic backgrounds.